2017
DOI: 10.1515/jpm-2015-0419
|View full text |Cite
|
Sign up to set email alerts
|

Role of collagen type IV in the pathogenesis of increased prenasal thickness in Down syndrome fetuses: sonographic and immunohistological findings

Abstract: Using the immunohistochemistry technique, we were able to confirm the overexpression of collagen type IV in the BM of the prenasal area. This may explain the sonographic finding of increased PT seen mainly in DS fetuses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The reason was reported that the use of PT/NBL ratio seen as a single and constant ratio was easier and more applicable method since PT increases together with the week of gestation and therefore a separate threshold value is required for each week of gestation. [5][6][7][8][9][10] Yang et al [12] also reported that PT/NBL ratio remained constant during 12-33 weeks of gestation (R=0.12; p>0.10) and 95th percentile value was 0.93. However, we found in our study that PT/NBL ratio displayed a weak but significant correlation with the week of gestation (R=0.25; p<0.01) and we calculated 95th percentile values of PT/NBL 1.1-0.9 during 16-23 weeks of gestation.…”
Section: Perinatal Journalmentioning
confidence: 92%
See 1 more Smart Citation
“…The reason was reported that the use of PT/NBL ratio seen as a single and constant ratio was easier and more applicable method since PT increases together with the week of gestation and therefore a separate threshold value is required for each week of gestation. [5][6][7][8][9][10] Yang et al [12] also reported that PT/NBL ratio remained constant during 12-33 weeks of gestation (R=0.12; p>0.10) and 95th percentile value was 0.93. However, we found in our study that PT/NBL ratio displayed a weak but significant correlation with the week of gestation (R=0.25; p<0.01) and we calculated 95th percentile values of PT/NBL 1.1-0.9 during 16-23 weeks of gestation.…”
Section: Perinatal Journalmentioning
confidence: 92%
“…[4] Recently, it has been reported that prenasal thickness (PT) as well as nuchal thickness can also be used as a marker in skin edema evaluation and the screening for Down syndrome [5] and that type IV collagen in basal membrane of prenasal skin tissues in cases with Down syndrome is significantly in high volume. [6] Persico et al [7] reported that PT increased significantly in fetuses with Down syndrome and that PT was >95th percentile in 73.1% of the cases. De Jong-Pleij et al [8] reported in their study that PT presented significant positive correlation with the week of gestation and prenasal thickness/nasal bone length (PT/NBL) ratio remained constant during the week of gestation, and emphasized that the PT/NBL ratio was >95th percentile in all of 30 fetuses with Down syndrome included in their study and PT/NBL ratio was a strong marker.…”
Section: Introductionmentioning
confidence: 99%